Emerging Nonsteroid-Based Procedural Therapies for Alopecia Areata: A Systematic Review. Issue 12 (December 2019) - Marchitto, Mark C.; Qureshi, Azam; Marks, Dustin; Awosika, Olabola; Rengifo-Pardo, Monica; Ehrlich, Alison
Abstract : BACKGROUND: Alopecia areata (AA) is a common form of patchy, nonscarring hair loss. Although intralesional steroid injections are currently the mainstay procedural therapy for AA, other nonsteroid-based procedural therapies, including platelet-rich plasma (PRP), ultraviolet radiation (UVR), and laser-based modalities, are emerging as practical options. OBJECTIVE: To systematically review nonsteroid-based procedural therapies for AA and recapitulate the available clinical data. MATERIALS AND METHODS: A systematic review of the literature was performed searching PubMed/MEDLINE databases identifying studies investigating PRP, UVR, and laser-based modalities for AA treatment. RESULTS: Literature search yielded 644 articles encompassing PRP, UVR, and laser treatment modalities for AA. Of the 644 articles, 46 met inclusion criteria. Although numerous reports demonstrate strong potential for PRP, UVR, and laser modalities in treating AA, high-quality evidence supporting their efficacy is still lacking. CONCLUSION: There is an abundance of evidence for nonsteroid-based procedural therapies in the treatment of AA. Randomized control trials comparing these treatment options head-to-head should be performed to better understand the true efficacy of these treatments.